A Hope Impact in MENA: Business Leadership and Job Performance - Akhras, Caroline; A.S.A. , Ferdous Alam (International Journal of Psychosocial Rehabilitation, 2020)
Research has shown that hope is a critical element in the business environment. This exploratory research study explores the role of hope focusing on leadership and job performance given that hope has established its conceptual independence and measurement discriminate validity. Even though research studies may have explored the role of hope for leaders and followers in the developed nations, research studies on the role of hope are new in the Middle East and North African Area. An essential component in the competitive business context, millennial leaders shape job performance, especially in the Middle East and North African Area (MENA). This case study focuses on the role of hope and job performance inside the business work units. As a research study, the aim of this paper is threefold: (1) whether the leader is perceived as implementing hope in the work life; (2) whether the followers perceive themselves as implementing hope in the work life (3) whether the level of hope is correlated to the level of job performance irrespective of gender. In line with this, three research questions were generated and belong to the faculty of business administration and economics. Sixty-one participants were employed in domestic or foreign companies in the Middle East and North African Area (MENA). Data was gathered using a survey. Based on the results, further research is recommended to better understand the nature of hope found in the local business context and its impact on job performance in the MENA workplace.